Wpływ terapii BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Studium przypadku = Effect of BEMER therapy on selected indicators of blood in the process of wellness after exercise endurance. Case study - Mirosław Mrozkowiak (Kazimierz Wielki University, 2015)
Mrozkowiak Mirosław. Wpływ terapii BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Studium przypadku = Effect of BEMER therapy on selected indicators of blood in the process of wellness after exercise endurance. Case study. Journal of Education, Health and Sport. 2015;5(4):278-298. ISSN 2391-8306. DOI: 10.5281/zenodo.17080 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A278-298 https://pbn.nauka.gov.pl/works/555193 http://dx.doi.org/10.5281/zenodo.17080 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015.   Wpływ terapii BEMER na wybrane wskaźniki krwi w ramach procesu odnowy biologicznej po wysiłku wytrzymałościowym. Studium przypadku   Effect of BEMER therapy on selected indicators of blood in the process of wellness after exercise endurance. Case study   Mirosław Mrozkowiak   Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska     Słowa kluczowe: terapia BEMER, wskaźniki krwi, odnowa biologiczna, wysiłek wytrzymałościowy, studium przypadku.   Keywords: BEMER therapy, blood indicators, wellness, exercise endurance, case study.   Streszczenie   Zasadniczymi naczyniami tworzącymi mikrokrążenie są naczynia włosowate. Pojedyncze naczynie włosowate ma średnicę około 6 p.m, sumaryczna powierzchnia przekroju naczyń włosowatych wynosi około 3000 cm2. Na każdy milimetr sześcienny ciała ludzkiego przypada średnio 600 naczyń włosowatych. Terapia systemem BEMR przy zastosowaniu kompleksowym lub uzupełniającym doskonali podstawowe procesy fizjologiczne, angiokinezę mikrokrążenia, doprowadzenie składników odżywczych i tlenu do komórek mięśniowych. Dzięki określonej modulacji biorytmicznej uzyskuje się synergiczny wpływ również na pierwotne i wtórne, nieco większe naczynia krwionośne. Materiał i metody. Badany mężczyzna realizujący zdrowy styl życia poddał się dwukrotnie pomiarowi wybranych wskaźników krwi i układu naczyniowego: po wysiłku wytrzymałościowym w czasie restytucji fizjologicznej oraz odnowie wspomaganej terapią BEMER. Uzyskane wyniki. Najbardziej znaczące zmiany w wybranych wskaźnikach krwi po wysiłku wytrzymałościowym zaobserwowano w: całkowitej ilości hemoglobiny najmniejsze w stężeniu jonów wodorowęglowych. Znamienne zmiany wystąpiły w okresie wczesnej odnowy we wskaźnikach: cząstkowym ciśnieniu tlenu (PO2), nasyceniu krwi tętniczej tlenem (SO2 (c)), oksyhemoglobinie (O2Hb), karboksyhemoglobinie (HbCO), methemoglobinie (MeHb) i hydroksyhemoglobinie (HHb).         Wnioski. Zastosowana metodyka i profil sygnału BEMER wpływa zróżnicowanie na wielkość wybranych cech krwi. Zastosowanie stymulacji BEMER w odnowie biologicznej po wysiłkach wytrzymałościowych u mężczyzn w 5-6 dekadzie życia może być uzasadnione i jako przygotowanie do wysiłku fizycznego.     Abstract   The principal vesels are forming capillary microcirculation. A single capillary has a diameter of about 6 pm, the total cross sectional area of the capillary is about 3000 cm2. For every cubic millimeter of the human body is an average of 600 capillaries. BEMR therapy system using the complex or complement excellent basic physiological processes angiokinesis microcirculation bringing nutrients and oxygen to muscle cells. With specific modulation biorhythmical synergistic effect is achieved also into primary and secondary, slightly larger vessels. Materials and methods. Tested man pursuing a healthy lifestyle surrendered twice selected indicators measure the blood and the vascular system: after exercise endurance during physiological restitution and renewal BEMER assisted therapy. The obtained results. The most significant changes in selected indicators of blood after endurance exercise was observed in the total amount of hemoglobin smallest hydrocarbyl ion concentration. Significant changes occurred during early recovery in the indicators: partial pressure of oxygen (PO2), arterial oxygen saturation (SO2 (c)), oxyhemoglobin (O2Hb), carboxyhemoglobin (HbCO), methemoglobin (MeHb) and hydroxyhemoglobin (HHB). Conclusions. Methodology and profile BEMER signal variation affects the size of the selected features of the blood. BEMER pacing in rejuvenating the efforts of strength in men in 5-6 decade of life may be justified, and in preparation for exercise.